Inflammatory effects of Salmonella typhimurium porins. - Galdiero, F (1990)
The inflammatory activity of porins purified from Salmonella typhimurium has been investigated. Porins (0.3 to 30 micrograms) injected into the rat paw induced a dose-related edema that was not due to lipopolysaccharide contamination and did not appear to be dependent on the activation of the complement system. The edema induced by 30 micrograms of porins was comparable to that caused by 1 mg of carrageenin and was inhibited by indomethacin (5 mg/kg) and dexamethasone (0.1 mg/kg). Porins (1 to 10 micrograms/ml) induced a concentration-related release of histamine from rat peritoneal cells. These results are discussed in the light of the possible pathogenic role of porins in infections.